2020
DOI: 10.1002/smll.202002124
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering of Partially Phosphidated Co@Co–P@NPCNTs for Highly Enhanced Electrochemical Overall Water Splitting

Abstract: Interface engineering is promising but still challenging for developing highly efficient and stable non‐noble‐metal‐based electrocatalysts for water splitting. Herein, partially phosphidated core@shell Co@Co–P nanoparticles encapsulated in bamboo‐like N, P co‐doped carbon nanotubes (denoted as Part‐Ph Co@Co–P@NPCNTs) are prepared through a pyrolysis–oxidation–phosphidation strategy. In this structure, each Co nanoparticle is covered with a thin Co–P layer to form a special core@shell heterojunction interface, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 45 publications
(48 reference statements)
0
39
0
Order By: Relevance
“…However, the Raman peaks of Ni 2 P cannot be detected, [35,36] which were perpetual to Ni 2 P. Noticeably, the Raman vibration of NiO cannot be observed in the Raman spectrum of NF-CNNOP sample but its intensity significantly decreases, suggesting the partial phosphidation of the ternary hybrid sample. [37,38] The cross-sectional morphological studies on the pristine NF and as-prepared samples are presented in Figure 1c-f to have detailed understanding of the surface morphological reaction. The pristine NF itself had an internal thickness of 3.20 µm.…”
Section: Synthesis and Morphological Studiesmentioning
confidence: 99%
“…However, the Raman peaks of Ni 2 P cannot be detected, [35,36] which were perpetual to Ni 2 P. Noticeably, the Raman vibration of NiO cannot be observed in the Raman spectrum of NF-CNNOP sample but its intensity significantly decreases, suggesting the partial phosphidation of the ternary hybrid sample. [37,38] The cross-sectional morphological studies on the pristine NF and as-prepared samples are presented in Figure 1c-f to have detailed understanding of the surface morphological reaction. The pristine NF itself had an internal thickness of 3.20 µm.…”
Section: Synthesis and Morphological Studiesmentioning
confidence: 99%
“…As the Ru content increases, the peak positions for Co 5 Ru 1 @NCNT/PF shift smoothly from hexagonal phases Co (PDF# 05-0727) to Ru (PDF# 06-0663). [3,30] Obviously, no Ru diffraction peaks can be found in XRD patterns of Co 5 Ru 1 @NCNT/PF, suggesting that the Ru atoms are incorporated into the Co lattice in the sample. [30][31][32] The morphology and size of as-synthesized samples are shown in Figure 1b-d.…”
Section: Preparation and Characterization Of Ru Doped In Co Matrix Su...mentioning
confidence: 99%
“…68 Unfortunately, the development of efficient bifunctional electrocatalysts to simultaneously promote HER and OER in the same electrolyte remains challenging. 69,70 Wang et al reported a bifunctional catalyst for HER and OER with Co NPs encapsulated in nitrogen-doped carbon (Co@N-C) which was prepared by pyrolysis of cobalt acetate and imidazole followed by acid leaching. 71 The unique encapsulation structure in Co@N-C leads to high activity and stability for HER in a wide pH range.…”
Section: Water-splitting Reactions In Confined Spacesmentioning
confidence: 99%